Comparison of anterior chamber depth measured by three different anterior segment analysis systems - Han Song; Wei Yang; Chunliu Yang; Qing Sun (Photodiagnosis and Photodynamic Therapy)
Purpose: This study aims to compare and evaluate the correlation and agreement among three distinct anterior segment analysis systems in measuring anterior chamber depth (ACD) in healthy myopic individuals. Methods: Myopic patients who underwent preoperative assessments at our hospital's refractive surgery department from January 2021 to December 2023 were included in this investigation. ACD was measured using three anterior segment analysis systems: Pentacam, Sirius, and IOLMaster 700. Statistical analyses were performed using SPSS software. The Pearson method was utilized to analyze correlations between the measured values of the three groups. Bland-Altman scatter plots were generated using MedCalc software, with 95 % limits of agreement applied to assess consistency among the datasets. Results: The mean anterior chamber depth (ACD) measured by the Pentacam, Sirius, and IOLMaster 700 was found to be 3.26 ± 0.26 mm, 3.30 ± 0.26 mm and 3.22 ± 0.25 mm, respectively. The mean ACD values obtained from these three devices exhibited statistically significant differences (p < 0.05). Furthermore, the ACD measurements from all three devices demonstrated a strong positive correlation with each other, p < 0.001, r = 0.965 (Pentacam and Sirius), r = 0.955 (Pentacam and IOLMaster 700), and r = 0.966 (Sirius and IOLMaster 700). The respective 95 % LoAs were -1.16 ∼ -0.73(Pentacam and Sirius);0.55 ∼ 1.05(Pentacam and IOLMaster 700);1.53 ∼ 1.96 (Sirius and IOLMaster 700). Conclusion: There is a high positive correlation between the anterior chamber depth (ACD) measured by three different anterior segment analysis systems in healthy myopic eyes. However, the differences in the measurement of different optical devices should be considered in clinical work, and it is not recommended to interchange them.